Determinants of dividend performance of financial sector in Malaysia / Ahmad Aiman Muslim Ab Rahim and Mohammad Afizi Ezwan Jasni - Ab Rahim, Ahmad Aiman Muslim; Jasni, Mohammad Afizi Ezwan (Faculty of Business and Management, 2019)
This study was conducted to identify the determinants of dividend performance of financial sector in Malaysia. The objective of this study is to identify the relationship between risk (BETA), cash flow (CF), debt (DER), investment (INV) and dividend (DPR). The secondary data were collected from Thomson Reuters DataStream and using quarterly starting from first quarter 2005 until fourth quarter 2017. The dependent variable is the dividend payout ratio which represents dividend performance. The independent variables were risk (BETA), cash flow (CF), debt (DER), and investment (INV). Using time series analysis, the finding shows that cash flow has positive relationship while risk (BETA), debt (DER) and investment (INV) has negative relationship with dividend performance. The result revealed that risk (BETA), cash flow (CF), debt (DER), and investment (INV) have significant effect towards dividend policy of financial sector in Malaysia. The findings from this study are useful to the board of directors and management team of companies in deciding an appropriate dividend policy for the company. The results are also useful to shareholders in making investment decisions.